SOCIO-ECOLOGICAL APPROACH TO INCREASE PARTICIPATION IN PREVENTING HIV TRANSMISSION FROM MOTHER TO CHILD IN KARO REGENCY, NORTH SUMATRA - Bebaskita Ginting1, R. Hamdani Harahap2, SarmaNursani Lumbanraja3, FazidahAguslina Siregar4, (Chelonian Research Foundation, 2024)
Transmission of the HIV virus from mother to child poses a heavy burden on public health due to the high mortality rate in children, especially those who do not receive therapy in the first age of life, so efforts to end the transmission of the HIV virus from pregnant women to children are an important milestone in ending the global epidemic by the elimination target set by WHO is the incidence of new infections <50/100,000 live births. The social-ecological framework takes a broad view of efforts to prevent mother-to-child transmission of HIV with a focus on various factors related to the program. This research aims to explore the participation of pregnant women, stakeholder participation and stakeholder barriers in efforts to prevent HIV transmission from mother to child. This research is qualitative research with a phenomenological study approach. In-depth interviews and FGDs were conducted with 32 informants consisting of Policy Makers at the Karo District Health Service, Health Workers, Health Cadres, Peer Support Cadres, Pregnant Women, Husbands of Pregnant Women, Community Figures and HIV Observer Organizations. Data were analyzed using Colaizzi's Method. The social-ecological approach contextualizes individual behavior using intrapersonal (e.g. knowledge, attitudes, behavior), interpersonal dimensions(social networks, social support), community (e.g. relationships between organizations/institutions), and public policy (e.g. implementation of Minister of Health regulations regarding mother-to-child HIV prevention programs) to provide a framework that describes interactions between layers so that solutions to individual problems not only found in the individual but solutions may be found in other layers where the individual lives and interacts. Creating sustainable health improvements will be most effective when all of these factors are targeted simultaneously. Keywords: Social Ecology, Prevention Mother To Child Transmission (PMTCT), Community leader participation,